MORPHO-PHYSIOLOGICAL FEATURES AND MEDICAL SIGNIFICANCE OF IXODIC MITES OF IXODES LATR. AND DERMACENTOR FABR. GENERATIONS – HUMANS AND ANIMALS ECTOPARASITES IN WESTERN UKRAINE - Федонюк, Л.Я.; Подобівський, С.С.; Корда, М.М.; Кліщ, І.М.; Андрейчин, М.А.; Шкільна, М.І. (World of Medicine and Biology, 2018)
The peculiarities of the structure of 124 females and 198 nymphs of mites of the Ixodes ricinus generation and also 58 females and 25 males of the Dermacentor reticulatus generation are studied. In the result of analysis of morphological indices of the Ixodes ricinus generation specimens some regularities in the ratio of total body length to the width of the abdomen at different degrees of saturation are found. For example, for the females is observed such correlation: 1:0,56; 1:0,59; 1:0,53; 1:0,6; 1:0,7. That correlation for nymphs is as follows: 1:0,56; 1:0,56; 1:0,58; 1:0,6; 1:0,58. So, for the females with rising of saturation degree increases not only the length of the abdomen, but also its width. The width of the abdomen increases very slowly and almost raises its length for the nymphs. For the females of the Dermacentor reticulatus generation the correlation of general body length to the abdomen width according to different degrees of saturation has the form: 1:0,69; 1:0,67; 1:0,65; 1:0,65: 1:0,81, that shows the relative proportion of these dimensions. Since May till October 2017 were studied 118 females, 174 nymphs and 3 larvae of the Ixodes ricinus generation to identify the pathogens of infectious diseases in them. Since 08.05.17 till по 03.07.17 were examined 179 mites, among of them 117 nymphs (31 % of cases were infected with Borelia organisms), 51 females (infected with Borelia organisms – 33 %) and 11 specimens were not infected such, as there were just some of their fragments. The sufferers were almost children. Researches were conducted to identify DNA of boreliosis and anaplasmosis pathogens. According to the results of amplification boreles and anaplasms were found in different life stages of the Ixodes ricinus generation. Borrelia Burgdorferi senso lato was detected in 37 cases, including adult mites – 11, nymphs – 25, not found – 1 case. Anaplasma phagocytophilum was detected in 15 cases, including adult mites – 5, nymphs – 9, unspecified – 1. Borrelia Miyamotoi was detected in 5 cases, among of them adult mites – 1 and nymphs – 4 cases. Since 10.07 till по 18.07 were examined 18 females, among of them the carriers of pathogens were 13, that was 72 % (Borrelia Burgdorferi – 9 specimens, Anaplasma phagocytophilum – 4). Among the infected females, three were simultaneously carriers of Borrelia Burgdorferi and Anaplasma phagocytophilum. During that period were examined also 27 nymphs, from which 10 (37 %) were carriers of pathogens, (1 - Borrelia Burgdorferi and 9 – Anaplasma phagocytophilum). The detected larva was not a carrier of Borelia organisms. Since 11.09 till 18.10 2017 were examined 84 mites, among of them 3 – Dermacentor reticulatus (2 females and 1 male) and 81 Ixodes ricinus, among of which 50 females, 1 larva and 30 nymphs. All the mites of the Dermacentor reticulatus generation were not the carriers of any of the pathogens. Among the all females of Ixodes ricinus the carriers of the pathogens were 16 examples that were 32 % (14 – Borrelia Burgdorferi, 1 – Anaplasma phagocytophilum, 1 – Borrelia Miyamotoi). From the 30 nymphs the carriers were just 8 samples that were 27 % (3 – Borrelia Burgdorferi, 3 – Anaplasma phagocytophilum, 1 – Borrelia Miyamotoi). It is worth to notice that in period since 2.10 till 18.10 among 22 examined females Ixodes ricinus only 5 (22 %) were carriers of Borrelia Burgdorferi, and among 7 nymphs just 1 (14 %) was infected by Borrelia Burgdorferi. From the body of children infected with mites two larvae were removed, one of which was the carrier of Anaplasma phagocytophilum. Additionally were examined 9 mites of Dermacentor reticulatus generation (5 females і 4 males), taken from a dog in May, and which were kept all the time in a frozen state. In the result of amplification the pathogen of Anaplasma phagocytophilum anaplasmosis was found. According to the analysis of frequency dynamics of mites infection of the Ixodes ricinus generation the carriers of infectious diseases, the rising of the mites and nymphs amount is noted, which are the carriers of the pathogens since May till July with an increase of average temperature from 18-230С till 25-270С and soon the frequency reducing of their infection since August till October at the temperature lowing to 20-150С. So, for mites of the genus Ixodes ricinus generation human ectoparasites are not only adult mites, but also nymphs and even larvae (the ratio of taken off the children nymphs and adult females – 2:1). The females of mites are more carriers of Borrelia Burgdorferi, and nymphs – of Anaplasma phagocytophilum and Borrelia Miyamotoi. Larvae can be human ectoparasites and transmit the pathogens of infections, particularly Anaplasma phagocytophilum. Males of the Dermacentor reticulatus generation can feed on the human body and carry the pathogens of anaplasmosis.